Monitoring COVID-19 Vaccine Acceptance in Kuwait During the Pandemic: Results from a National Serial Study [Erratum] - AlAwadhi E; Zein D; Mallallah F; Bin Haider N; Hossain A (Dove Medical Press, 2021)
AlAwadhi E, Zein D, Mallallah F, Bin Haider N, Hossain A. Risk Manag Healthc Policy. 2021;14:1413—1429. The authors have advised the city listed for affiliation 3 on page 1413 is incorrect. The text “Hanoi” should read “Hawalli”. This error was introduced by the Editorial staff during the publication process. Read the original article